2013
DOI: 10.1007/s13659-013-0029-4
|View full text |Cite
|
Sign up to set email alerts
|

ent-Kaurane diterpenoids from the plant Wedelia trilobata

Abstract: Abstract:Four new ent-kaurane diterpenoids, namely, 3α-tigloyloxypterokaurene L 3 (1), ent-17-hydroxy-kaura-9(11),15-dien-19-oic acid (2), and wedelobatins A (3) and B (4), together with 11 known ent-kaurane diterpenoids (5-15), were isolated from the ethanol extract of Wedelia trilobata. All the structures of 1-15 were elucidated on the basis of spectroscopic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 15 publications
0
7
0
1
Order By: Relevance
“…Thirteen known compounds were identified as 3 α ‐tigeloyloxy‐9 β ‐hydroxy‐ ent ‐ kaura ‐16‐ en ‐19‐oic aicd ( 3 ), 4, 5‐di‐ O ‐caffeoyl ‐ quinic acid methyl ester ( 4 ), 3,4‐di‐ O ‐caffeoylquinic acid methyl ester ( 5 ), 3,4‐di‐ O ‐caffeoylquinic acid butyl ester ( 6 ), 3‐ O ‐caffeoylquinic acid butyl ester ( 7 ), methyl caffeate ( 8 ), epifriedelanol ( 9 ), β ‐D‐glucopyranosyl‐3‐ O ‐[ β ‐D‐xylopyranosy‐l‐(1→2)‐ β ‐D‐glucuronopyranosyl] oleanolate ( 10 ), stigmasterol ( 11 ), stigmasterol‐3‐ O ‐ β ‐D‐glucopyranoside ( 12 ), kaempfer‐ ol‐3‐ O ‐ β ‐D‐glucopyranoside ( 13 ), 7‐methoxyl‐kaempferol‐3‐ O ‐ β ‐D‐glucopyranoside ( 14 ), isoquercetin‐3‐ O ‐ β ‐D‐glucoside ( 15 ) by comparing their MS, NMR, and specific rotation data with those of related compounds in literatures.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen known compounds were identified as 3 α ‐tigeloyloxy‐9 β ‐hydroxy‐ ent ‐ kaura ‐16‐ en ‐19‐oic aicd ( 3 ), 4, 5‐di‐ O ‐caffeoyl ‐ quinic acid methyl ester ( 4 ), 3,4‐di‐ O ‐caffeoylquinic acid methyl ester ( 5 ), 3,4‐di‐ O ‐caffeoylquinic acid butyl ester ( 6 ), 3‐ O ‐caffeoylquinic acid butyl ester ( 7 ), methyl caffeate ( 8 ), epifriedelanol ( 9 ), β ‐D‐glucopyranosyl‐3‐ O ‐[ β ‐D‐xylopyranosy‐l‐(1→2)‐ β ‐D‐glucuronopyranosyl] oleanolate ( 10 ), stigmasterol ( 11 ), stigmasterol‐3‐ O ‐ β ‐D‐glucopyranoside ( 12 ), kaempfer‐ ol‐3‐ O ‐ β ‐D‐glucopyranoside ( 13 ), 7‐methoxyl‐kaempferol‐3‐ O ‐ β ‐D‐glucopyranoside ( 14 ), isoquercetin‐3‐ O ‐ β ‐D‐glucoside ( 15 ) by comparing their MS, NMR, and specific rotation data with those of related compounds in literatures.…”
Section: Resultsmentioning
confidence: 99%
“…12,13) In this study, the remaining fractions were further separated with an octadecyl silane (ODS) column followed by preparative HPLC (ODS) to give compounds 10 (3. The structures of compounds 10-19 were identified as ent-3β-angeloyloxykaur-16-en-19-oic acid, 18) ent-3βtigloyloxykaur-16-en-19-oic acid, 18) 3α-cinnamoyloxypterokaurene L 3 , 18) pterokaurene L 3 , 19) 3α-angeloyloxypterokaurene L 3 , 18) 3α-tigloyloxypterokaurene L 3 , 20) ent-kaur-9(11),16dien-19-oic acid, 21) ent-17-hydroxykaur-15-en-19-oic acid, 22) tetrachyrin, 23) and 15-hydroxykaur-9(11),16-dien-19-oic acid, 22) respectively, by comparing their spectroscopic data with reported values (Fig. 1).…”
Section: Isolation Of Compounds 1-19 From Indonesian Wedelia Prostratamentioning
confidence: 99%
“…1). Further bioassayguided separation afforded ten more ent-kaurene diterpene derivatives (10)(11)(12)(13)(14)(15)(16)(17)(18)(19) (Fig. 1) from the remaining fractions of the Indonesian W. prostrata.…”
mentioning
confidence: 99%
“…Seed production is low and generally does not reproduce prolifically via seed [4]. It really is utilized by Indians as traditionally in the treatment of backache, muscle cramp, rheumatism, stubborn wounds, sores, swelling and arthritic pain, fever and malaria [5][6][7]. So far, phytochemical studies have revealed some structurally diverse chemicals from this plant, including terpenoids (sesqui-, diter-, and triterpenoids), steroids, flavonoids and phenolics, some of which showed significant bioactivities [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It really is utilized by Indians as traditionally in the treatment of backache, muscle cramp, rheumatism, stubborn wounds, sores, swelling and arthritic pain, fever and malaria [5][6][7]. So far, phytochemical studies have revealed some structurally diverse chemicals from this plant, including terpenoids (sesqui-, diter-, and triterpenoids), steroids, flavonoids and phenolics, some of which showed significant bioactivities [7][8][9][10][11][12][13]. Numerous pharmacological activities of W. trilobata offers been reported such as antimicrobial [14], Antioxidant [15], Anti-inflammatory [15], wound healing [16], Anthelmintic [17] and anticancer [15].…”
Section: Introductionmentioning
confidence: 99%